Weakening trends of glacier and snowmelt-induced floods in the Upper Yarkant River Basin, Karakoram during 1961–2022 - Ying Yi; Yu Zhu; Shi-Yin Liu; Muhammad Saifullah; Kun-Peng Wu; Qiao Liu; Jin-Yue Wei (Advances in Climate Change Research, 2025)
Glacier and snowmelt-induced floods (GSFs) in glacierized regions are highly sensitive to climate change, yet their dynamics in areas such as the Upper Yarkant River Basin (UYRB) remain inadequately understood. Existing studies are constrained by data limitations and oversimplified modeling approaches, underscoring the need for a comprehensive analysis of the long-term changes in GSFs to improve flood risk management and water resource planning in the UYRB. This study investigated the characteristics, temporal changes, and climatic responses of GSFs based on a well-validated hydrological model. Results reveal that GSFs in the UYRB experienced a weakening trend from 1961 to 2022, as indicated by decreases in flood peak, duration, volume, and frequency. Although a portion of GSFs were primarily driven by snow runoff, the majority were mainly governed by glacier runoff. Among the examined climatic factors, temperature during the flood period was the key factor influencing GSF changes. Notably, despite the overall warming and wetting trend in the UYRB, temperatures during GSF events showed a decreasing trend, which suppressed glacier runoff and contributed to the weakening trends of GSFs. Spatial analysis identified the 4500–6000 m a.s.l. elevation zone as hydrologically critical, accounting for approximately 71% of the total runoff during the flood season. Under a 2 °C warming scenario, the intensity of GSFs is expected to increase across all return periods, with greater increases for longer return periods. A 10% increase in precipitation is projected to marginally enhance the intensity of GSFs with return periods of 20 years or less, while decreasing the intensity of extreme floods with 50- to 100-year return periods. Conversely, a 10% decrease in precipitation will reduce the intensity for all return periods. When the 2 °C warming scenario is combined with ±10% changes in precipitation, intensity of GSFs rises across all return periods, with more pronounced effects for longer return periods—especially under conditions of increased precipitation. These findings are pivotal in shaping effective strategies for flood adaptation and mitigation in alpine river basins.